ATTRACTING INVESTORS IN TERRITORIAL MARKETING - YAKUSHEVSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the conditions of economic instability caused by the spread of the COVID-19 pandemic and military actions by the russian federation on our territory, local government authorities feel the impact of the "belt-tightening" strategy implemented by the central government. Faced with their own financial difficulties, the center reduces transfers, which were previously the main source of funds for supporting infrastructure and overall urban development. Therefore, territorial bodies aspiring to development must actively work on creating a positive image of their territory to diversify sources of capital and attract new investors. In this context, territorial marketing to attract investors is promotion (advertising). In turn, promotion is the fourth element of the implementation of territorial marketing, but it requires utilizing the entire marketing mix (the "4P" concept). When considering the first element of the implementation of territorial marketing, it is worth mentioning that many regions of our country can offer themselves to investors through so-called territories with preferential investment regimes. Thus, the task of forming the "territory for the investor" product will include two main components: the territory as a whole and territories with special regimes. To conduct pricing effectively, it is necessary to have a good understanding of investment projects and possess up-to-date information about the market. "Place" - location or placement - is the most complex and difficult concept in territorial marketing. While the placement of the territory cannot be controlled, the flow of resources passing through this territory, forming growth points, can be managed. Certainly, in business, promotion and advertising activities are more technologically advanced than in the public sector, but this is quite natural. There will be no significant differences because attracting a professional from the advertising market for government or local self-government is easier than a marketer working with the strategic block. However, if private practices and techniques are quite successful, more conceptual issues of promotion significantly lag behind. As in business, in territorial product management, it is advisable to use all available means, even if it is a small budget for advertising and a few exhibitions per year. However, marketing of territorial products, especially in attracting investors, is a complex task that is effectively solved comprehensively and sequentially, guided by the marketing mix.